Sistem Informasi Keuangan Terintegrasi dengan Dukungan Sistem Pengambilan Keputusan (DSS) dalam Organisasi - Peter . (Jurnal Manajemen Maranatha, 2008)
Management Information System (MIS) in organization very important, to distribute information from one division to the other’s. Inside MIS we can find other subsystem which delivered and distributed organization financial information, that called Financial Information System (FIS). FIS made for the efficiency and effective financial report and give the decription of organization condition and position in financial. FIS can be integrated in all system of organization and it can be design with or without Decision Support System (DSS). FIS with DSS can helping the user’s speciality for top management as the decision maker, such as Manager or Director.